Antioxidant, gene expression and metabolomics fingerprint analysis of Arabidopsis thaliana treated by foliar spraying of ZnSe quantum dots and their growth inhibition of Agrobacterium tumefaciens - Kolackova, Martina; Moulick, Amitava; Kopel, Pavel; Dvorak, Marek; Adam, Vojtech; Klejdus, Borivoj; Huska, Dalibor (Journal of hazardous materials, 2019)
Nanotechnology, new fascinating field of science, is bringing many application's options. However, it is necessary to understand their potential environmental risk and toxicity. Zinc selenide quantum dots (ZnSe QDs) are getting valuable due to wide industrial usage, mainly as cadmium free diodes or stabilizing ligand. Thanks to unique properties, they could also open the possibilities of application in the agriculture. Their effects on living organisms, including plants, are still unknown. Therefore, the attention of this work was given to antioxidant response of Arabidopsis thaliana to 100 and 250 μM ZnSe QDs foliar feeding. ZnSe QDs treatment had no statistically significant differences in morphology but led to increased antioxidant response in the leaves at the level of gene expression and production secondary antioxidant metabolites. Concurrently, analysis of growth properties of Agrobacterium tumefaciens was done. 250 μM ZnSe solution inhibited the Agrobacterium tumefaciens viability by 60%. This is the first mention about effect ZnSe QDs on the plants. Although QDs induced oxidative stress, the apply treatment dose of ZnSe QDs did not have significant toxic effect on the plants and even no morphological changes were observed. However, the same amount of ZnSe QD induced an inhibitory effect on Agrobacterium tumefaciens.
Keywords: Gene Expression; Arabidopsis; Antioxidants; Quantum Dots; kvantové tečky; Arabidopsis thaliana; A. tumefaciens; Agrobacterium tumefaciens; Selenium Compounds; Zinc Compounds; antioxidancia; metabolomika; sloučeniny zinku; ZnSe QDs; Metabolomics; exprese genu; Toxicity; sloučeniny selenu